The Role of Patriotic Education in the Civic Self-Realization of University Students - Stepan Gennadievich Chukhin (Сибирское юридическое обозрение, 2011)
Modernization theory and the practice of patriotic education in Russia is associated with the processes of integration of Russian society in the international educational space. Perceptions of the Western European model of civil society involves the expansion of the problematic field of patriotic education. Problems of patriotic education should include a wide range of issues of civil socialization and self-realization, and not limited to the military-political component. Young students should be prepared to implement a patriotic position in various situations of civil choice.